2020
DOI: 10.1016/j.celrep.2020.107596
|View full text |Cite
|
Sign up to set email alerts
|

The Cation Channel TMEM63B Is an Osmosensor Required for Hearing

Abstract: Highlights d TMEM63B is a hypo-osmolarity-activated cation channel d Deficiency of TMEM63B causes hearing loss in mice d TMEM63B is localized in hair cells and required for outer hair cell survival d TMEM63B mediates Ca 2+ -dependent regulatory volume decrease in outer hair cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 75 publications
4
103
1
Order By: Relevance
“…The Q/R editing affects Ca 2+ permeability of Tmem63b channel Tmem63 family are osmosensitive (or mechanosensitive) cation channels (27,39). Their plant orthologue OSCA channels are also osmosensitive and mechanosensitive (39)(40)(41).…”
Section: Presence Of Exon 4 Suppresses Q/r Editing In Tmem63bmentioning
confidence: 99%
See 1 more Smart Citation
“…The Q/R editing affects Ca 2+ permeability of Tmem63b channel Tmem63 family are osmosensitive (or mechanosensitive) cation channels (27,39). Their plant orthologue OSCA channels are also osmosensitive and mechanosensitive (39)(40)(41).…”
Section: Presence Of Exon 4 Suppresses Q/r Editing In Tmem63bmentioning
confidence: 99%
“…We recently demonstrated that Tmem63s are osmosensitive cation channels activated by hypotonic stress and mediate extracellular Ca 2+ influx (27). We have established that the most sensitive measurement for the osmosensitivity was the percentage of cells responding to hypotonic stress (27).…”
Section: The Splicing and Editing Regulate Hypoosmolarity-induced Ca mentioning
confidence: 99%
“…New ion channels are continuously being uncovered. For instance, it was recently shown that the stretch-activated nonselective cation channel TMEM63B is an osmosensor that can mediate the Ca 2+ influx [101]. This example indicates that it cannot be excluded that genes coding for Ca 2+ -transport proteins and contributing to Ca 2+ signaling were missed in the present work.…”
Section: Discussionmentioning
confidence: 77%
“…region replaced by eGFP after the start codon [20]. At P3, both homozygous Pou4f3(Δ/Δ) and Pou4f3(-/-) showed extensive degeneration of hair cells, while hair cells of both heterozygous mice were normal ( Fig 3A and 3B).…”
Section: Plos Geneticsmentioning
confidence: 98%
“…Pou4f3 knockout mice were generated by replacing the coding sequence after start codon by EGFP [20]. Mice used in this study were either maintained on C57BL/6J background or a mixed background of C57BL/6J and FVBN.…”
Section: Animalsmentioning
confidence: 99%